Defining and predicting short-term alcohol use changes during a smoking cessation attempt. (September 2015) - Berg, Kristin M.; Piper, Megan E.; Smith, Stevens S.; Fiore, Michael C.; Jorenby, Douglas E.
Abstract: Introduction: Alcohol and nicotine are commonly used substances in the U.S., with significant impacts on health. Using both substances concurrently impacts quit attempts. While studies have sought to examine changes in alcohol use co-occurring with tobacco cessation, results have not been consistent. Understanding these changes has clinical implications. The objective of this study is to identify changes in alcohol consumption that occur following tobacco cessation, as well as predictors of alcohol use patterns following a smoking cessation attempt. Methods: A secondary analysis of a randomized, placebo-controlled trial evaluating the efficacy of five tobacco cessation pharmacotherapies. Participants ( N  = 1301) reported their smoking and alcohol consumption daily for two weeks prior to, and two weeks after, the target quit date (TQD). Results: Generally, alcohol use decreased post-TQD. Smokers who reported less pre-quit alcohol use, as well as smokers who were female, non-white, and had a history of alcohol dependence tended to use less alcohol post-quit. Pre- and post-quit alcohol use were more strongly related among men and among those without a history of alcohol dependence. Conclusions: For most smokers alcohol use decreased following smoking cessation. These results suggest that the expectation should be of decreased alcohol use post cessation. However, attention may be warranted for those who drink higher amounts of alcohol pre-cessation because they may be more likely to drink more in the post-quit period which may influence smoking cessation success. Highlights: Alcohol use decreased in the two weeks following tobacco cessation. Post-quit alcohol use was positively correlated with pre-quit alcohol use. Women and those with a history of alcohol dependence drank less post-quit. Participants who self-identified as non-white drank less post-quit.